Burnout Syndrome Perawat Selama Masa Pandemi - Raditya Kurniawan Djoar; Anastasia Putu Martha; farhan rizky romadhoni (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
COVID-19 is a contagious disease and was declared a pandemic by WHO on March 11, 2020. In handling COVID-19 patients, health workers, especially nurses, have a high risk of contracting due to longer working hours than usual and the pressure felt that causes burnout syndrome in nurses while handling COVID-19 patients. The purpose of this study was to identify nurses' burnout syndrome during treatment in COVID-19 patients. This research was conducted in 2022 at St. Vincent A Paulo Catholic STIKES Surabaya with a population of 137 people. The method used is purposive sampling technique and uses Maslach Burnout Inventory (MBI) questionnaire of 31 questions using Likert scale model. The presentation of data from the results of the study includes the general characteristics of respondents and specific data. The results showed that 137 people had experienced mild burnout syndrome with a percentage of 83.9% in terms of personality factors and general characteristic factors which included high expectations and heavy burden on work. It is hoped that hospital/clinic management will be able to manage the conditions experienced by health workers by providing assistance to be able to refocus the expectations of health workers to be more realistic so that burnout syndrome conditions can be avoided and health workers can remain productive in their work even during a pandemic.